Gender-bending aubergines: molecular phylogenetics of cryptically dioecious Solanum in Australia - Martine, Christopher T; Anderson, Gregory J; Les, Donald H (Australian systematic botany, 2009)
The causes, consequences and correlates of dioecy have been the subject of much discussion since the days of Darwin. Several recent authors have stressed the importance of informing this body of theory, with studies focusing on lineages in which both dioecy and hermaphroditism are present. The genus Solanum is an ideal group for analysis, because dioecy, hermaphroditism and potential unisexual transitions (e.g. andromonoecy) among them all occur. Phylogenetic hypotheses are presented for the Australian species in Solanum subgenus Leptostemonum (the 'spiny solanums') section Melongena, which contains 10 of the 14 currently described dioecious species in the genus. Phylogenetic analysis of the ITS and trnK-matK gene regions supports a single origin of dioecy from andromonoecy in Australian Solanum. The causes, mechanisms, and maintenance of dioecy in Australian Solanum are explored, including the role of past climate change in the establishment of centres of endemism.